Diabetes mellitus in a dog: case report (Research, Society and Development, 2023)
The objective of this article is to report the case of a female dog, 9 years and 3 months old, with Diabetes Mellitus, mixed breed (SRD), her clinical signs and complementary exams, who arrived at a private clinic in the city of Lagarto-SE with ketoacidosis. and performed the use of FreeStyle Libre® to assess blood glucose during treatment. Diabetes Mellitus is one of the most frequent endocrinopathies and is characterized by an increase in the level of glucose in the blood, caused by problems in the secretion of insulin or in the action of this hormone, being of high importance in veterinary medicine and can cause alterations mainly in the carbohydrates and proteins of these animals. . The clinical signs of this disease are related to polydipsia, polyphagia and polyuria, in addition to other types of complications such as vascular disease, pancreatitis, ketoacidosis, cachexia and cataracts, and if not treated, it can lead the animal to death. The diagnosis is defined by evaluating the patient's blood glucose, clinical signs and the presence of glucose in the urinary test. Veterinary follow-up to correct the ketoacidosis condition, together with the use of the aforementioned device, was effective in measuring blood glucose, the patient did not experience any adversities and her clinical condition was stabilized.